A General Model to Calculate the Spin–Lattice Relaxation Rate (R1) of Blood, Accounting for Hematocrit, Oxygen Saturation, Oxygen Partial Pressure, and Magnetic Field Strength Under Hyperoxic Conditions. Issue 5 (1st October 2021) - Bluemke, Emma; Stride, Eleanor; Bulte, Daniel P.
Abstract : Background: Under normal physiological conditions, the spin–lattice relaxation rate (R1) in blood is influenced by many factors, including hematocrit, field strength, and the paramagnetic effects of deoxyhemoglobin and dissolved oxygen. In addition, techniques such as oxygen‐enhanced magnetic resonance imaging (MRI) require high fractions of inspired oxygen to induce hyperoxia, which complicates the R1 signal further. A quantitative model relating total blood oxygen content to R1 could help explain these effects. Purpose: To propose and assess a general model to estimate the R1 of blood, accounting for hematocrit, SO2, PO2, and B0 under both normal physiological and hyperoxic conditions. Study Type: Mathematical modeling. Population: One hundred and twenty‐six published values of R1 from phantoms and animal models. Field Strength/Sequence: 5–8.45 T. Assessment: We propose a two‐compartment nonlinear model to calculate R1 as a function of hematocrit, PO2, and B0. The Akaike Information Criterion (AIC) was used to select the best‐performing model with the fewest parameters. A previous model of R1 as a function of hematocrit, SO2, and B0 has been proposed by Hales et al, and our work builds upon this work to make the model applicable under hyperoxic conditions (SO2 > 0.99). Models were assessed using the AIC, mean squared error (MSE), coefficient of determination ( R 2 ), and Bland–Altman analysis. The effect of volume fraction constants W RBC and W plasma was assessed by the SD of resulting R1. The range of the model was determined by the maximum and minimum B0, hematocrit, SO2, and PO2 of the literature data points. Statistical Tests: Bland–Altman, AIC, MSE, coefficient of determination ( R 2 ), SD. Results: The model estimates agreed well with the literature values of R1 of blood ( R 2 = 0.93, MSE = 0.0013 s −2 ), and its performance was consistent across the range of parameters: B0 = 1.5–8.45 T, SO2 = 0.40–1, PO2 = 30–700 mmHg. Data Conclusion: Using the results from this model, we have quantified and explained the contradictory decrease in R1 reported in oxygen‐enhanced MRI and oxygen‐delivery experiments. Level of Evidence: 3 Technical Efficacy: Stage 1